Record Information System of Barangay Novaliches Proper: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Why do researchers choose a Record Information System? Because the Barangay is using alog book or a manual process of recording information, researchers want to upgrade it into acomputerized system to make their records a lot easier. The main goal of the researchers'study is to develop a system that will alter the record-keeping method so as to supplyeconomics. Moreover, the system is going to be ready to secure residents' confidentialrecords, to simply update residents’ profiles, and to provide backup information for all records.The main aim of creating the Barangay Record Information System is to provide an efficientand organized way for the barangay to manage and store resident information. The BarangayRecord Information System was specifically designed to digitally store resident information ina secure and centralized database, allowing barangay officials to access and maintain recordsas needed without the limitations and inconvenience of traditional paper-based methods. Thissystem presents various benefits by digitizing resident information and incorporating it into anall-inclusive database. It simplifies the process of data entry and retrieval while reducing therisk of errors, data loss, and inconsistencies that often arise from manual record-keepingmethods. Additionally, the system features a user-friendly interface, enabling authorizedpersonnel to easily manage and access resident records while ensuring the privacy andsecurity of data.The Record Information System of Barangay Novaliches Proper will give safer storage ofrecords and fast retrieval of files, maintain reliability and accuracy, and track files faster. Thiswill be very useful to the staff, from handwritten records and manual issuing of barangayclearance and certificates, as well as the income and expense reports, to an automatedprocessing system.
Keywords: IT & Management